Changing paradigms in understanding Chinese imperial law. Issue 9 (29th July 2022) - Jiang, Yonglin
Abstract: This essay evaluates and critiques the studies of Chinese imperial law in line with Edward Said's proposition of 'Orientalism'. It identifies three major stages: the classical legal Orientalism, emphasising the heterogeneity of Chinese and Western laws based on Western values; the 'neo-legal Orientalism', stressing the homogeneity of the two by taking Western culture also as the assessment standard; and Oriental legalism, seeking Chinese subjectivity with Chinese perspectives and resources. The changes of the paradigms in assessing the legal culture in pre-republican China are related to the general intellectual transformations in the contemporary world. This essay proposes the approach of 'confluent legalism' that features drawing on diverse cultural essences of various nations in the world.